2015
DOI: 10.1080/00131881.2015.1076994
|View full text |Cite
|
Sign up to set email alerts
|

Educational outcomes and functioning of bi-ethnic Dutch children in school

Abstract: Background: Changing demographics in societies through international migration have led to an increasing number of bi-ethnic individuals. The focus of this study is on bi-ethnic students with one parent with an ethnic majority background and one parent with an ethnic minority background. Most studies worldwide have grouped these bi-ethnic students with ethnic minority students or have grouped them according to the ethnic background of their mothers with the majority or minority group. However, empirical argume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…Additionally, greater experience with diversity could be related to higher citizenship competence (Geijsel et al 2012). Karssen et al (2015) found that bi-ethnic students differ in citizenship competences from mono-ethnic majority and mono-ethnic minority students. Bi-ethnic students scored higher on citizenship competences than mono-ethnic majority students but lower than mono-ethnic minority students.…”
Section: Ethnic Composition Of the Familymentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, greater experience with diversity could be related to higher citizenship competence (Geijsel et al 2012). Karssen et al (2015) found that bi-ethnic students differ in citizenship competences from mono-ethnic majority and mono-ethnic minority students. Bi-ethnic students scored higher on citizenship competences than mono-ethnic majority students but lower than mono-ethnic minority students.…”
Section: Ethnic Composition Of the Familymentioning
confidence: 99%
“…Therefore, in addition to insight into the diversity within this group, we also provide insight into the relationship between the ethnicity and gender of the migrant parent and the educational outcomes and social functioning of bi-ethnic students. Studies of bi-ethnic students and school outcomes, and social functioning in school have, to the best of our knowledge, focused only on differences between mono-ethnic minority, mono-ethnic majority and bi-ethnic students (e.g., Pearce-Morris and King 2012; Schlabach 2013; Karssen et al 2015) and have not yet sufficiently explored differences among bi-ethnic students from families with different compositions. Important reasons for this lack of literature are due to data limitations and to the assumption that bi-ethnic students can be understood and referred to as ethnic minority students (e.g., for a review, see Stevens et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have categorized bi-ethnic students as minority students. In the study by Karssen et al (2015), it was found that bi-ethnic students with one migrant and one non-migrant parent cannot be simply grouped together with mono-ethnic minority students. Bi-ethnic students were found to score higher on cognitive outcomes and on social-emotional functioning in school than monoethnic minority students.…”
Section: Introductionmentioning
confidence: 99%
“…Their early experiences with ethnic diversity could make them more open and accustomed to ethnic differences (Barnes, 2001). Because Karssen, Van der Veen, and Volman (2015) found that bi-ethnic students with one migrant and one non-migrant parent cannot be simply grouped together with mono-ethnic minority students, the focus of this study is on bi-ethnic children with one nonmigrant parent (with two non-migrant grandparents) and one migrant parent (with two foreign grandparents).…”
Section: Introductionmentioning
confidence: 99%